(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
This study aims to develop an English learning model using the concept of gamification in a Vocational High School in the Kalijati Subang area. The concept of gamification will be applied to learning English vocabulary so that learning is more interesting and fun. The design of this gamified system will use Marczewski’s Gamification Framework. Framework that has user types with learning and self-development needs. Game mechanics in these user types such as levels, challenges, and rewards can support users of the gamified system in achieving goals. The tests that have been carried out have shown success in applying the Marczewski framework to the user’s functional needs. This study uses a quasi-experimental method using a nonequivalent control group design in a quantitative approach.